2007
DOI: 10.4049/jimmunol.178.5.2641
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-1 Receptor-Associated Kinase 4 Structures Reveal Novel Features and Multiple Conformations

Abstract: IL-1R-associated kinase (IRAK)4 plays a central role in innate and adaptive immunity, and is a crucial component in IL-1/TLR signaling. We have determined the crystal structures of the apo and ligand-bound forms of human IRAK4 kinase domain. These structures reveal several features that provide opportunities for the design of selective IRAK4 inhibitors. The N-terminal lobe of the IRAK4 kinase domain is structurally distinctive due to a loop insertion after an extended N-terminal helix. The gatekeeper residue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 23 publications
7
87
0
Order By: Relevance
“…Previously, Cheng et al (10) identified Thr-342, Thr-345, and Ser-346 by MS analysis, and other groups identified these residues by crystallography (19,22). In this report, we present several lines of evidence to support the hypothesis that autophosphorylation of IRAK4 is required for the full activation and subsequent signaling events in a cell type-specific manner.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previously, Cheng et al (10) identified Thr-342, Thr-345, and Ser-346 by MS analysis, and other groups identified these residues by crystallography (19,22). In this report, we present several lines of evidence to support the hypothesis that autophosphorylation of IRAK4 is required for the full activation and subsequent signaling events in a cell type-specific manner.…”
Section: Discussionsupporting
confidence: 69%
“…We used compound 1, a previously characterized inhibitor of IRAK4 kinase for our studies on the pharmacology of IRAK4 in human cells (19). This compound is highly potent against IRAK4 (IC 50 ϭ 2 nM at K m ϭ 300 M ATP) (22) and to a lesser extent IRAK1 (IC 50 ϭ 15 nM at K m ϭ 35 M ATP). Although it possesses excellent selectivity, it has poor physical properties such as solubility and permeability, which necessi- Ϫ/Ϫ human dermal fibroblasts.…”
Section: Pharmacological Inhibition Of Irak4 Kinase Blocks Irak4 Phosmentioning
confidence: 99%
“…Domain constructs covering the minimal catalytic domains of BRI1, BRL1, and BAK1 were identified using structure-based sequence alignments against the human IRAK4 (PDB-ID 2OID) (Kuglstatter et al 2007) and tomato Pto (PDB-ID 2QKW) kinases (Xing et al 2007) using the program EXPRESSO (http://www.tcoffee.org). The resulting kinase domain fragments were cloned into vector pETM11, providing an N-terminal 6xHis tag and a tobacco etch virus protease (TEV) site.…”
Section: Recombinant Protein Expression and Purificationmentioning
confidence: 99%
“…To fine-map the binding surface of BKI1-CT, we constructed a BRI1 homology model based on the crystal structure of human IRAK4 kinase (Kuglstatter et al 2007). We found that most sequence differences between BRI1 and BRL1 map to the C-lobe of the kinase (Fig.…”
Section: Bki1 C-terminal Tail Binding To Bri1 Inhibits Interaction Wimentioning
confidence: 99%
“…In addition, BIK1 shares 36% identity with the cytoplasmic domain of BAK1 (BRI1-associated kinase 1) and 39% identity with the BAK1 kinase-domain sequence that has been crystallized (PDB entry 3uim; Yan et al, 2012). We are currently solving the crystal structure of BIK1 by molecular replacement using BAK1 (PDB entry 3uim) and IRAK4 (PDB entry 2oib; Kuglstatter et al, 2007) as search models. Additionally, we are currently pursuing co-crystallization of BIK1 with ATP analogues.…”
Section: Resultsmentioning
confidence: 99%